Make your own Twine games! - Anthropy, Anna (No Starch Press, Inc., 2019)
"A playful, kid-friendly introduction to game development using Twine, a free online scripting tool for creative storytelling. Author is a well-known professional game designer. Make Your Own Twine Games! shows you how to make interactive fiction games using Twine, a beginner-friendly online tool for creating non-linear stories. Readers use basic web scripting to design choose-your-own-adventure games using author's games as examples. Anthropy walks readers through game development process from start to finish, covering everything from mapping out a game's structure and story to debugging the end product. Readers will understand what makes designing video games challenging and fun, and will feel ready to bring their own game ideas to life"--